What is wrong with virtual water trading? - Erik Gawel; Kristina Bernsen (Helmholtz-Zentrum für Umweltforschung (UFZ), 2011)
So-called virtual water, the water embedded in internationally traded goods, has come under discussion. The amount of quantitative studies which attempt to estimate volumes and flows of virtual water in relation to agricultural trade is rising rapidly, while the concept has been recognized by large firms and international institutions. From the viewpoint of economic trade theory, the endowment with abundant water resources gives countries a comparative advantage in the export of waterintensive goods, while water scarce countries gain the option to alleviate stress on domestic water resources by substituting the production of water-intensive goods by imports. However, fairness implications are seen to arise in the reallocation of water resources through the means of mostly agricultural trade. In this perspective, moral problems can be attached to both imports and exports, and even to a country's own consumption of virtual water. Global institutional arrangements are therefore suggested, to regulate virtual water flows in a "fair" and "efficient" manner. This paper will give a short overview of the concept's history and findings, and subsequently analyse it from the perspective of economic trade and resource theory. The contribution of this paper will be to examine the concept of virtual water in terms of the problems it evokes, its informative value and the policy suggestions which are made in this context. It must be concluded that the concept is unspecific and inconsistent, implying governance schemes which will neither improve efficiency nor sustainability in today's trade patterns.
Keywords: F18; Q25; Q27; Q56; 330; virtual water; water footprint; international trade; global water governance